Analisis Campur Kode Tuturan Guru di Kelas VII dalam Kegiatan Pembelajaran Bahasa Indonesia di SMP Negeri 13 Kupang - Jemima Sofiani Nenotek; Labu Djuli; Alex Djawa (Jurnal Lazuardi, 2026)
This Study aims to describe the types of code mixing and the functions of code mixing in the speech of Indonesian language teachers in grade VII of SMP Negeri 13 Kupang. This study user quatitative descriptive approach with date collection teachhinques in the form od observation, interviews, recordings, and documentation. The date obtained were teacher speech containing code mixing during the laerning process. The results showed that there were two types of code mixing used by teacher 1) inner code mixing in the form of inserting Kupang malay elements, 2) outer code mixing in the form of using words or phrases from Inggris. The forms of code mixing found included the insertion of words, phrases, clauses, interrogative, sentences, and imperative sentences. The functions od code mixing include 1) Building familiarity anf social interaction, 2) providing instruction of commands, 3) explaining the meaning of learning material, 4) expressing feelings and emotions.